Urgent Business : Five Myths Business Needs to Overcome to Save Itself and the Planet - Thomson, Ian, 1962- (Bristol University Press, 2022)
Combining academic insight and inspiring real-world examples this book offers a new business model which argues that all companies should become responsible businesses, transforming the sustainability agenda into a more holistic and systemic approach.